1962
DOI: 10.1115/1.3684335
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Diabatic Flow in an Annulus With an Inner Rotating Cylinder

Abstract: The present paper is part of the second phase of an investigation of the phenomena and variables which control the rate of heat transfer in the air gap of a rotating electrical machine. Experimental data for diabatic flow in an annulus are summarized and compared with the results of previous studies. The data are examined in terms of the types of flow processes occurring in an annulus, and it is found that the results for diabatic flow clearly confirm those obtained for adiabatic flow in showing the existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(95 citation statements)
references
References 0 publications
11
77
0
Order By: Relevance
“…The vertical axis is defined as a dimensionless height (a) Air gap mesh with groove slots at stator and rotor surfaces that the slots increase the temperature gradients at the wails. This improves the rate of heat transfer [9] in the annular flow.…”
Section: Mesh Velocity Vectors and Temperature Proffiesmentioning
confidence: 96%
“…The vertical axis is defined as a dimensionless height (a) Air gap mesh with groove slots at stator and rotor surfaces that the slots increase the temperature gradients at the wails. This improves the rate of heat transfer [9] in the annular flow.…”
Section: Mesh Velocity Vectors and Temperature Proffiesmentioning
confidence: 96%
“…The Nusselt number for tangential air flow between concentric cylinders is given by Becker and Kaye [15] as a function of the Taylor number:…”
Section: Figure 2 Axial and Radial Thermal Networkmentioning
confidence: 99%
“…Jeng et al (2007) performed heat transfer measurement over the inner cylinder for Re=60-2400 and Ta =0-2922 with and without ribs by using thermocouples. Becker and Kaye (1962) experimentally showed that for Re=0-5900 and Ta =65-1175 the Nusselt number declined along with the through-flow Reynolds number and reached minimum (at Re=1592) before it increased again. Simmers and Cony (1979) experimentally showed that the Nusselt number decreased with the increase of the through-flow Reynolds number and it was nearly constant beyond a certain value of the through-flow Reynolds number for Re=0-3000 and Ta =200-6500.…”
Section: Introductionmentioning
confidence: 99%